Pediatric metanephric adenoma with Fanconi–Bickel syndrome: a case report and review of literature - Osama M. Sarhan; Ahmed Al Farhan; Salma Abdallah; Hamzah Al Ghwanmah; Deena Boqari; Helmy Omar; Abdulmohsin Al Faddagh; Hanan Al Kanani; Fouad Al Kawai (Surgical Case Reports)
Abstract Background Metanephric adenoma (MA) is a rare benign renal tumor that resembles renal cell carcinoma and Wilms’ tumor in radiological as well as pathological appearance. It can present at any age or gender, and it is extremely rare in the pediatric age group with less than 50 reported cases. Fanconi–Bickel syndrome (FBS) is a rare autosomal recessive disorder of carbohydrate metabolism. Herein, we report a rare incidence of MA in a boy with a genetically confirmed FBS who underwent a nephron-sparing surgery. Case presentation A 21-month-old boy was referred to the pediatric urology clinic for further evaluation of an incidentally discovered left renal mass. His laboratory investigations showed normal renal function, hypophosphatemia, high blood glucose level, markedly elevated serum alkaline phosphatase, and low serum vitamin D. Blood picture showed signs of polycythemia and urinalysis showed glucosuria and aminoaciduria. Genetic testing was positive for Fanconi–Bickel syndrome. Radiological investigations were carried out with abdominal ultrasound and computerized tomography (CT) with intravenous contrast documented a sharply marginated peripheral hypoechoic hypovascular homogeneously enhancing mass at the upper pole of the left kidney measuring 2.0 × 1.8 × 2.0 cm. The child was admitted and started on supportive treatment until his medical condition was stabilized, then underwent elective open left partial nephrectomy via a left upper transverse abdominal transperitoneal incision. The excised renal mass was sent for histopathological assessment and was found to be a tumor composed of tightly packed tubules with no mitotic figures or necrosis and scanty cytoplasm consistent with MA. After good hydration and tumor resection, his polycythemia gradually improved. The patient was discharged home in a good condition with his proper replacement therapies. His follow-up abdominal ultrasound after 12 months showed no signs of recurrence. Conclusions Metanephric adenoma is extremely rare in the pediatric age group, especially in those who have a FBS. The only way to diagnose and treat this tumor is by surgical resection as most patients are asymptomatic. A nephron-sparing surgery is better for this age group in which the future renal function is considered.